Evaluasi Intensitas Regulasi Lingkungan dalam Mendorong Pengungkapan Informasi Akuntansi Lingkungan pada Industri Kerajinan Kayu di Kecamatan Rejoso Kabupaten Nganjuk - Luluk Mushfiroh; Hwihanus Hwihanus (AKUNTANSI 45, 2026)
This study aims to analyze the intensity of environmental regulations and their influence on the disclosure of environmental accounting information in woodcraft businesses located in Rejoso District, Nganjuk Regency. The study is based on the fact that woodcraft production activities generate waste such as sawdust and involve the use of chemical finishing materials, while compliance with environmental regulations and environmental reporting remains low. The research employed a qualitative method with a case study approach focusing on two enterprises, UD Nizam Utama and UD Toni Jaya. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that the intensity of environmental regulations in both businesses is at a moderate level; however, the implementation remains informal, undocumented, and unsupported by standardized operational procedures. UD Nizam Utama demonstrates relatively better practices through partial recording of environmental costs and the utilization of wood waste as fuel, while UD Toni Jaya lacks any form of environmental cost documentation. Overall, the disclosure of environmental accounting information in both businesses remains low due to limited knowledge, insufficient socialization, and the absence of external reporting requirements. This study underscores the need to strengthen the capacity of MSMEs and integrate environmental regulations to encourage sustainable environmental reporting practices.